Glia-related mechanisms in the anteroventral cochlear nucleus of the adult rat in response to unilateral conductive hearing loss - Fuentes-Santamaría, Verónica; Alvarado, Juan C.; López-Muñoz, Diego F.; Melgar-Rojas, Pedro; Gabaldón-Ull, María C.; Juiz, José M. (Frontiers in Neuroscience, 2014)
Conductive hearing loss causes a progressive decline in cochlear activity that may result in functional and structural modifications in auditory neurons. However, whether these activity-dependent changes are accompanied by a glial response involving microglia, astrocytes, or both has not yet been fully elucidated. Accordingly, the present study was designed to determine the involvement of glial related mechanisms in the anteroventral cochlear nucleus (AVCN) of adult rats at 1, 4, 7 and 15 d after removing middle ear ossicles. Quantitative immunohistochemistry analyses at light microscopy with specific markers of microglia or astroglia along with immunocytochemistry at the electron microscopy level were used. Also, in order to test whether trophic support by neurotrophins is modulated in glial cells by auditory activity, the expression and distribution of neurotrophin-3 (NT-3) and its colocalization with microglial or astroglial markers was investigated. Diminished cochlear activity after middle ear ossicle removal leads to a significant ipsilateral increase in the mean gray levels and stained area of microglial cells but not astrocytes in the AVCN at 1 and 4 d post-lesion as compared to the contralateral side and control animals. These results suggest that microglial cells but not astrocytes may act as dynamic modulators of synaptic transmission in the cochlear nucleus immediately following unilateral hearing loss. On the other hand, NT-3 immunostaining was localized mainly in neuronal cell bodies and axons and was upregulated at 1, 4 and 7 d post-lesion. Very few glial cells expressed this neurotrophin in both control and experimental rats, suggesting that NT-3 is primarily activated in neurons and not as much in glia after limiting auditory activity in the AVCN by conductive hearing loss.